TRANSPORTASI OJEK DI DAERAH AIE DINGIN KECAMATAN LEMBAH GUMANTI KABUPATEN SOLOK - Iswandi, Harry; Rianto, Slamet; Juita, Erna (Pendidikan Geografi, 2013)
This research was conducted with the following objectives: 1) To determine the reasons people chose motorcycle transportation. 2) To determine the safety and comfort of people choosing motorcycle transportation. 3) To determine affordability / accessibility and means of transport for the motorcycle community. This research is qualitative by using snow ball (snowball) research informants are people who thought a lot of research to find information about the theme. Determination of informants that the information must be taken in accordance with the characteristics of qualitative research with key informants motorcycle taxi drivers and people who travel by motorcycle. Data were collected by interview and documentation. Results of the study to determine 1) the reasons people choose a motorcycle taxi transportation to the place of destination communities facilitate quicker, easier and delivered to the address, 2) To determine the safety and comfort of motorcycle taxis transport chosing felt very safe and comfortable and satisfying for passenger, 3 ) To determine affordability / accessibility and public transportation motorcycle for transportation reach motorcycles passed to facilitate the public up to the place that can not be in the public transportation pass and take passengers anywhere.